Sublingual immunotherapy to house dust mite as an immunological intervention in refractory atopic dermatitis (Indian Journal of Case Reports, 2019)
Sublingual immunotherapy (SLIT) with house dust mite (HDM) preparation has been shown to reduce disease severity in patients with atopic dermatitis (AD). A 5-year-old girl with severe Atopic Dermatitis refractive to all possible pharmacotherapy was put on SLIT for dust mite and followed up for a period of one year. SLIT to dust mite proved highly effective in reducing the disease severity score as well as prevention of exacerbations in this patient.